EXPRESSION OF MATRIX METALLOPROTEINASES IN LACRIMAL FLUID AND GENE POLYMORPHISM OF COMPLEMENT FACTOR H (CFH) IN PATIENTS WITH PRIMARY OPEN-ANGLE GLAUCOMA - V. A. Sokolov (SPb RAACI, 2017)
The objective of our study was to evaluate production of matrix metalloproteinase–2 and -9 in  lacrimal fluid, as well as СFH gene polymorphism in a group of patients with primary open-angle glaucoma.  The study was performed with 120 eyes of patients with primary open-angle glaucoma (POAG) including  34 eyes from the first-stage disease; 35 eyes, from the 2nd stage; 35, at the 3rd stage of the disorder, and 16  eyes with stage 4 POAG. Control group consisted of 25 glaucoma-free patients. Tear fluid served as a material  for biochemical tests. The levels of MMP-2 and MMP-9 were determined by sandwich ELISA for the both  eyes. Venous blood was used for genetic studies. Genomic human DNA was isolated from the whole blood  leukocytes, a polymerase chain reaction (PCR) was performed.  The results of this study were analyzed using a package of SAS applied statistical programs (Statistical  Analysis System, SAS Institute Inc., USA) employing standard algorithms of variation statistics, i.e., correlation  analysis, contingency tables, and various types of intergroup comparisons for the parameters studied. The  following results were obtained: average indices for metalloproteinases-2 and -9 were found to be increased upon  progression of the disease. Correlation analysis of contingency relationships was performed for morphometric,  clinical, functional parameters, and quantitative indices of MMP-2 and MMP-9. We also studied prevalence  of CFH gene polymorphismic alleles depending on the stage of glaucoma development. One may conclude  that our study provided evidence for a relationship between MMP-2 and MMP-9 production, and СFH  gene polymorphism, thus expanding a list of host genetic mutations which could be potentially involved into  pathogenesis of primary open-angle glaucoma.